O processo de construção de um plano de estudo sobre costumes alimentares na perspectiva da educação científica intercultural em uma escola família agrícola do município de Anchieta – ES - Zetóles, Maíra Gaigher (2021)
This research aims to analyze a Study Plan development experience on “Family’s Alimentation Behaviours” held with a 6th year students group of an Agricultural Family School at Espirito Santo State, Brazil. As the basis for the research development, theoretical references are being used such as Paulo Freire’s reference matrix (FREIRE, 1987), the assumptions of Intercultural Scientific Education – ISE (AIKENHEAD, 1996, 2000) and for the concepts of culture and traditional knowledge, Cunha (2017) and Almeida (2010). Qualitative research has been used as a methodological approach, inspired by participant research based on Brandão (2017), due to the link with Popular Education. The data has been produced through observations registered in field journal, school control sheets and written records produced by the students (questionnaire and synthesis). The subjects participating in the research were 14 students enrolled in the 6th year of this school, residents of neighboring peasant communities and also the school teacher, researcher/author of this work. The data has been analyzed according to the theoretical assumptions of the ISE and cultural levels established by Brandão (2017) and described by Brazil (2019). The analyses indicated the creation of "cultural bridges" between school knowledge and traditional knowledge and that alimentation in peasant communities involves, in addition to biological factors, social and cultural factors of these communities’ identity. As an Educational Product, we are proposing a didactic manual on the Study Plan and its practice in Agricultural Family Schools that work with Alternation Pedagogy, emphasizing the possibilities of application within ISE perspective in several other contexts.